Natural Law: New Directions in Thomistic Theological Ethics - Charles R. Pinches (Journal of Moral Theology, 2016)
This essay considers three Thomistic thinkers who are helpful in establishing the proper location of natural law in theological context: Jean Porter, Servais Pinckaers and Herbert McCabe. Of these, Porter’s work is the most recent and likely the best known. It is helpful, I argue, but takes a certain turn that separates it from the context of Christian theology.  The work of Pinckaers and McCabe, in that order, helps tether natural law more thoroughly to Thomas’s theologically informed understanding. Both also thoughtfully open new directions for the further exploration of natural law today.